Comparison of self-reported lifetime concussions and mild traumatic brain injuries among adults. (23rd February 2023) - Daugherty, Jill; Sarmiento, Kelly; Breiding, Matthew
ABSTRACT: Introduction: The reliability of self-reported brain injury data relies on how well people interpret the questions. Objective: This study examines how different yet commonly used questions may impact traumatic brain injury (TBI) estimates. Methods: Self-report data were collected from 4, 053 respondents in the summer wave of Porter Novelli's 2020 ConsumerStyles survey. Respondents were randomized to be asked about lifetime experience of either concussion or mild TBI (mTBI) and then asked follow-up questions. Results: Approximately 25.5% of respondents reported sustaining a concussion in their lifetime while 17.2% reported an mTBI. The circumstances of the injuries, such as location and mechanism of injury, were similar. A greater percentage of individuals who were asked about concussions (91.1%) reported receiving a diagnosis for their most serious injury compared to those who were asked about diagnosis of an mTBI (69.9%). Discussion: A greater percentage of respondents reported a lifetime history of concussion than mTBI. More respondents with a lifetime history of concussion reported receiving a diagnosis. These results suggest that the terminology used can impact reporting. These findings suggest that there is a meaningful difference in the understanding of the terms 'concussion' and 'mild TBI, ' with people perceiving mTBI as a more serious injury.